Ganga water pollution: A potential health threat to inhabitants of Ganga basin. (August 2018) - Dwivedi, Sanjay; Mishra, Seema; Tripathi, Rudra Deo
Abstract: Background: The water quality of Ganga, the largest river in Indian sub-continent and life line to hundreds of million people, has severely deteriorated. Studies have indicated the presence of high level of carcinogenic elements in Ganga water. Objectives: We performed extensive review of sources and level of organic, inorganic pollution and microbial contamination in Ganga water to evaluate changes in the level of various pollutants in the recent decade in comparison to the past and potential health risk for the population through consumption of toxicant tainted fishes in Ganga basin. Methods: A systematic search through databases, specific websites and reports of pollution regulatory agencies was conducted. The state wise level of contamination was tabulated along the Ganga river. We have discussed the major sources of various pollutants with particular focus on metal/metalloid and pesticide residues. Bioaccumulation of toxicants in fishes of Ganga water and potential health hazards to humans through consumption of tainted fishes was evaluated. Results: The level of pesticides in Ganga water registered a drastic reduction in the last decade (i.e. after the establishment of National Ganga River Basin Authority (NGRBA) in 2009), still the levels of some organochlorines are beyond the permissible limits for drinking water. Conversely the inorganic pollutants, particularly carcinogenic elements have increased several folds. Microbial contamination has also significantly increased. Hazard quotient and hazard index indicated significant health risk due to metal/metalloid exposure through consumption of tainted fishes from Ganga. Target cancer risk assessment showed high carcinogenic risk from As, Cr, Ni and Pb as well as residues of DDT and HCHs. Conclusion: Current data analysis showed that Ganga water quality is deteriorating day by day and at several places even in upper stretch of Ganga the water is not suitable for domestic uses. Although there is positive impact of ban on persistent pesticides with decreasing trend of pesticide residues in Ganga water, the increasing trend of trace and toxic elements is alarming and the prolong exposure to polluted Ganga water and/or consumption of Ganga water fishes may cause serious illness including cancer.